Design of Dual Band Meta-Material Resonator Sensor for Material Characterization - Sucitra R. Harry; Zahriladha Zakaria; Maizatul Alice M. Said; Rammah Alahnomi; M. Harris Misran (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper describes the design and implementation of the dual band metamaterial resonator for sensing applications by employing perturbation theory in which the dielectric properties of resonator affect Q-factor and resonance frequency. The designed sensor operates at two resonance frequency 3.20 GHz and 4.18 GHz in the range of 1 GHz to 5.5 GHz for testing solid materials. The Computer Simulation Technology (CST) software is used to design and model this sensor and it was analyzed by using vector network analyzer (VNA) for testing measurement. This study uses empirical equation from the tested materials with well-known permittivity to estimate the permittivity of other materials with unknown permittivity. The proposed sensor has achieved a narrow band with high Q-factor value of 642 and 521 at the operating frequencies of 3.16 GHz and 4.18 GHz respectively. These findings are compared with findings of previous study and the proposed sensor has achieved a high sensitivity and accuracy of 80% compare to others. This is proof that this senor could be used to characterize materials and sensing applications.